Surgeons and Their Tools: A History of Surgical Instruments and their Innovators. Part III: The Medical Student's Best Friend—Retractors. Issue 1 (January 2015) - El-Sedfy, Abraham; Chamberlain, Ronald S.
This is the third of five manuscripts reviewing the historical origins of some of the more commonly used surgical instruments and takes "time out" to remind current surgeons about the surgical pioneers on whose shoulders they now stand and whose inventions they now use.